2016
DOI: 10.4103/0019-5278.197531
|View full text |Cite
|
Sign up to set email alerts
|

Internet use at workplaces and its effects on working style in indian context: An exploration

Abstract: Background:Internet use has revolutionized the pattern of working style at the workplace. It led to an increased use for nonprofessional activities at the workplace. It has been shown to affect productivity at the workplace. There is a dearth of literature from the Indian context in this area.Aim:This study was conducted to explore the pattern of Internet use at the workplace and its dysfunctions.Setting and Design:The present study was a cross-sectional prospective study.Materials and Methods:The objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In an era where every minute is crucial for the organizations, spending the supposedly productive working hours for unproductive Internet activities for personal use by the employees has emerged as a major problem for the organizations. As per Shrivastava, Sharma, and Marimuthu (2016), 57 per cent of Indian workers agree that Internet activities make them delay their work, and another study found that 89% of the US employees agreed that they waste their time every day by engaging into nonwork-related Internet activities (Salary.com, 2014). Monetary losses to the companies are enormous, and it was estimated that they suffer a loss of US$759 billion annually because of cyberloafing activities (Martin, Brock, Buckley, & Ketchen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In an era where every minute is crucial for the organizations, spending the supposedly productive working hours for unproductive Internet activities for personal use by the employees has emerged as a major problem for the organizations. As per Shrivastava, Sharma, and Marimuthu (2016), 57 per cent of Indian workers agree that Internet activities make them delay their work, and another study found that 89% of the US employees agreed that they waste their time every day by engaging into nonwork-related Internet activities (Salary.com, 2014). Monetary losses to the companies are enormous, and it was estimated that they suffer a loss of US$759 billion annually because of cyberloafing activities (Martin, Brock, Buckley, & Ketchen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from India and abroad also support the current study findings. ( 3 , 31 ) A study conducted in southern India among employees ( n =250) of various organizations, who were using internet for minimum a year, found that overall delay for going to the sleep was 1.6 hours for the sample. ( 31 ) Another exploratory survey conducted among nurse educator students ( n =49) in Finland, reported daily usage of social media for many hours among nursing and other professional students.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to the studies done in India till now. [31] However, as to our knowledge, this is the first study from India focusing on internet addiction, sleep disturbances, and EDS. A few studies done from India assessing internet addiction and psychiatric comorbidities showed relation of internet overuse and personality characteristics,[32] depression, anxiety, well-being, and functioning.…”
Section: Discussionmentioning
confidence: 99%